Effect of passive tobacco smoke on the incidence of respiratory adverse events in female patients undergoing general anesthesia– a cohort study - Maryyam Hanif; Samina Ismail (BMC Anesthesiology)
Abstract Background Passive smoking is linked to increased respiratory adverse events (AEs) during general anesthesia (GA). This study aims to assess whether females exposed to passive tobacco smoke undergoing GA, experience a higher incidence of perioperative respiratory AEs. Methods This single-center prospective cohort study was conducted from July 2021 to July 2022, at a University Hospital. After approval from the ethical review committee, 150 female patients receiving GA for elective surgeries requiring endotracheal intubation were included and classified into Passive Smoking Exposure (PSE) and Non-Passive Smoking Exposure (NPSE) groups. Data on respiratory adverse events (AEs) including laryngospasm, bronchospasm, breath holding, desaturation, hypersecretion, coughing, wheezing, and stridor during the perioperative period was collected using a proforma. Statistical analysis was performed using RStudio with Chi-square, Fisher’s exact test, and Mann-Whitney U test to determine significance. Results Among 150 female participants, 75 were included in the PSE and 75 in the NPSE groups. The PSE group had an overall statistically significant incidence of respiratory AEs compared to the NPSE group (69.3 vs. 16.0%, p < 0.001). Hypersecretion (50.7% vs. 4%) and desaturation (38.7% vs. 6.7%) intraoperatively and desaturation (14.7% vs. 1.3%) and cough (10.7% vs. 0% ) in the post-anesthesia care unit (PACU) were significantly more common in the PSE group (p < 0.001). At 12 h postoperatively, 56% of the PSE group had respiratory issues versus 32% in the NPSE group (p < 0.05). Conclusion Passive smokers had a significantly higher incidence of perioperative respiratory AEs with GA, necessitating the need for preoperative strategies to address passive smoke exposure.